Carbon isotopic fractionation by desorption of shale gases. (February 2015) - Wang, Xiaofeng; Li, Xiaofu; Wang, Xiangzeng; Shi, Baoguang; Luo, Xiaorong; Zhang, Lixia; Lei, Yuhong; Jiang, Chengfu; Meng, Qiang
Abstract: Geochemical studies of shale gas and conventional reservoirs within the Triassic Yanchang Formation of Xiasiwan and Yongning Field, Ordos Basin show that methane is isotopically depleted in 13 C as compared to δ 13 C1 calculated by the Ro based on the relationship between δ 13 C1 and Ro. Geochemical fractionation during the adsorption/desorption process of shale system may play a significant part in influencing δ 13 C1 values of shale gas. Two shale core samples from confined coring of the Yanchang Formation were adopted segmented desorption experiments to examine this phenomenon. The results show that the δ 13 C1 of desorbed gas changes little in the first few phases of the experiments at low desorption levels, but become less negative rapidly when the fraction of desorbed methane exceeds 85%. The desorption process for the last 15% fraction of the methane from the shale samples shows a wide variation in δ 13 C1 from −49‰ to −33.9‰. Moreover, δ 13 C1 of all desorbed methane from the shale samples is substantially depleted in 13 C than that calculated by Ro, according to Stahl and Carey's δ 13 C1 –Ro equation for natural gas generated from sapropelic organic matter. This shows some gases with isotopically enriched in 13 C cannot be desorbed under the temperature and pressure conditions of the desorption experiments. This observation may be the real reason for the δ 13 C1 of shale gases and conventional reservoirs becomes more negative in Xiasiwan and Yongning Fields, Ordos Basin. The magnitude of the deviation between the δ 13 C1 of shale gas and that calculated by Ro may be related to the adsorption capacity of shale or the proportion of absorbed gases. In this way, we may be able to evaluate the relative adsorption capacity of shale in geological conditions by δ 13 C1 of the shale gas, or by δ 13 C1 of conventional gas which generated by the shale with certainty. The δ 13 C1 of conventional gas in Dingbian and Yingwang Fields have no deviation because the TOC value of the hydrocarbon source rock is relatively low. Highlights: The δ 13 C1 of shale gases is generally depleted in 13 C than that calculated by Ro. There are some gases with a less negative δ 13 C value in the shale that cannot be desorbed. We may be able to assess the adsorption capacity of shale by δ 13 C1 of the shale gas.